Экономическая устойчивость коммунального сектора экономики - Chaadaeva V. V. (Scientific studies: from theory to practice, 2016)
The questions and defines the concept of "economic sustainability of municipal economy" as one of the most important industries in which is concentrated the production, distribution and consumption of most of energy resources.
Keywords: развитие; предприятие; enterprise; development; жилищно-коммунальное хозяйство; экономическая устойчивость; функционирование; operation; economic sustainability; housing and communal services